SHOOT TIPS DERIVED-SOMATIC EMBRYOGENESIS IN MASS PROPAGATION OF DENDROBIUM INDONESIA RAYA ‘INA’ - Rachmawati, Fitri; Purwito, Agus; Wiendy, Ni Made Armini; Mattjik, Nurhayati Anshori; Winarto, Budi (Emirates Journal of Food and Agriculture, 2015)
A mass propagation protocol of Dendrobium Indonesia Raya ‘Ina’ via somatic embryogenesis pathway in producing high qualified-seedlings was successfully established. Three different explant sources harvested from plantlets viz. shoot tips, lateral shoots and young leaves; half strength Murashige and Skoog (MS) and Vacin and Went (VW) basalt media; thidiazuron (TDZ) of 1.0, 1.5, and 2.0 mg/L; N6-benzylaminopurine (BAP) of 0.5 and 1.0 mg/L; kinetin (KIN) of 0.5 and 1.0 mg/L were tested for embryogenic callus (EC) initiation. TDZ (0, 0.1, 0.3 and 0.5 mg/L) and BAP (0, 0.05 and 0.1 mg/L) combination and callus densities of 1, 2, 3 and 4 g/25 ml liquid media were studied for EC proliferation. Three, five, ten and fourteen days period and 5 ± 2 °C, 18 ± 2 °C, and 24 ± 2 °C of desiccation were investigated for conversion of EC to somatic embryo (SE) and germination of SE. The VW, haft-strength MS, Growmore® (32N:10P:10K), Rosasol®, and Hyponex® containing 150 ml/L coconut water (CW) were used for plantlet preparation. Results of the studies revealed that shoot tips derived from in vitro plantlets cultured on half-strength MS semi-solid medium supplemented with 1.5 mg/L TDZ and 0.5 mg/L BAP resulted in the shortest of EC initiation time of 9.3 days after culture and 100% explant regeneration with 0.41 g EC fresh weight, and 4.27 mm3 volume of EC. Rapid growth and proliferation of EC was highly possible by culturing the 3 g EC per 25 ml in the half strength MS liquid medium fortified by 0.50 mg/L TDZ, 0.10 mg/L BAP, and 150 ml/L CW with 11.91 g fresh weight of EC, 9.91 g EC added, and 3.97 multiplication rate. The optimal conversion of EC into SEs as high as 92.7% with 35.9 SEs per clump and 86.9% SE germination with 31.2 germinated-SEs per clump were easily determined by culturing 7 days EC desiccation at 18 ± 2 °C on the half strength MS medium containing 0.05 mg/L BAP with conversion time of 12.7 days for EC into SEs and 19.3 days for germination. The best performance of plantlet growth with 7.07 cm height of plantlets, 5.15 cm leaf length, 8.67 number of roots, 5.30 cm root length, 0.71 g fresh weight of plantlets, and 0.076 g dry weight of plantlets was significantly noticed on 2 g/L Hyponex® medium containing 150 ml/L CW. The plantlets were successfully transferred to ex vitro condition on Cycas rumphii bulk with 91,6% survival rate. The established protocol is high possibly applied for other Dendrobium hybrids.